1958
DOI: 10.1002/ange.19580701602
|View full text |Cite
|
Sign up to set email alerts
|

Nachbargruppen‐Effekte in der organischen Chemie

Abstract: Zahlreiche Reaktionen der organischen Chemie verlaufen abnormal, wenn eine geeignete Gruppe dem Reaktionszentrum nahe ist. Durch intramolekulare Herstellung einer Hauptvalenzbindung von der Nachbargruppe zum Reaktionszentrum entstehen ringförmige Zwischenprodukte, deren Auftreten die Struktur des Produkts und die Stereochemie des Reaktionsverlaufs sowie dessen Geschwindigkeit entscheidend beeinflussen. Nachbargruppen können Atome oder Liganden mit einsamen Elektronenpaaren, Doppelbindungen und auch Wasserstoff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
1

Year Published

1960
1960
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(7 citation statements)
references
References 164 publications
0
6
0
1
Order By: Relevance
“…Since oxygen substituents are less effective neighboring group participants than nitrogen-centered groups, the addition of N -hydroxyamidines 7 instead of amidines 2 to 1 was expected to proceed without rearrangement, because they would add with the more nucleophilic hydroxy group attacking on 1 …”
mentioning
confidence: 99%
“…Since oxygen substituents are less effective neighboring group participants than nitrogen-centered groups, the addition of N -hydroxyamidines 7 instead of amidines 2 to 1 was expected to proceed without rearrangement, because they would add with the more nucleophilic hydroxy group attacking on 1 …”
mentioning
confidence: 99%
“…Again no reaction takes place at the stereocenter, and therefore enantiomeric purity can be assumed to be retained from the starting material. Application of the same reaction conditions to 19 gave ( S )-[2-(dimethylamino)-1-phenylethyl]cyclopentadiene as a 1:1 mixture of the isomers 21 instead of ( S )-[2-(dimethylamino)-2-phenylethyl]cyclopentadiene, caused by reaction via the intermediate aziridinium ion 20 . Because of the complete inversion at the stereogenic center, the absolute configuration of the product is S .
1 Possible diastereomeric forms of the complexes 1−4 (M = Ca, Sm, Yb; E = OMe, NMe 2 ).
…”
Section: Resultsmentioning
confidence: 99%
“…[7] It is also applicable with a wide range of neighboring groups such as heteroatoms, arenes, cyclopropanes and norbornyl groups. [8][9][10][11][12][13][14] In these transformations, achieving regioselectivity towards the blue position during the nucleophilic attack on the cationic intermediate is crucial. The control of the regioselectivity could be thermodynamically controlled when the leaving group can act as the nucleophile, rendering the reaction reversible.…”
Section: Inversion Via Rearrangementsmentioning
confidence: 99%
“…[15] This pioneering work did not consider the stereochemical aspects of NGP, but subsequent studies showed that the participation by heteroatoms can result in retention or inversion of configuration following the rearrangement explained above. [8] In this section, we will examine representative cases involving common heteroatoms such as oxygen, nitrogen, and bromine. However, the principles discussed can potentially be applied to other heteroatoms that lead to inversion, like sulfur [16] and chlorine.…”
Section: Heteroatom Participationmentioning
confidence: 99%